Development of digital twin ecosystem and ontology in medicine - Mammadova, Masuma Huseyn; Ahmadova, Aytan Adil (OU Scientific Route, 2023)
Providing citizens with high-quality and safe medical services, providing information support for medical research and continuous medical education, making both doctor’s decisions and management decisions necessitated the provision of tools to ensure complex digitization of healthcare. To achieve these goals, a wide range of modern technologies have emerged. One such technology is digital twin technology. Modern medicine, being formed in the environment of Health 4.0, includes not only the treatment of patients, but also the management of healthcare, the prevention of diseases and the processes of health restoration. With the increasing popularity of information communication technologies, people’s demand for health services is shifting from offline service to new online models. Currently, the field of online medicine is not developed enough to serve the elderly, chronically ill people and the people with infectious diseases. Using the advantages of digital twins in solving these problems can give positive results. The article describes the nature, capabilities and applications of digital twin technology. The principles of the formation of the medical digital twin ecosystem are developed to ensure citizens’ accessibility to medical services and to make both medical and managerial decisions. The architecture and structural components of the digital twin ecosystem providing the connection between physical medical objects (patient, hospital, doctor, etc.) and their virtual images are shown. An ontological model for the staged construction and functionalization of the general DT of healthcare is proposed and its hierarchical architecture is established.